Implicit Cost Allocation and Bidding for Contracts - Cohen, Susan I.; Loeb, Martin (Management Science, 1990)
The question of how, or even whether, indirect costs should be allocated for pricing decisions has been controversial and unresolved. This paper takes a step toward answering this question by examining the special case of a firm that must incur incremental fixed costs to complete any or all of the several projects for which it is submitting simultaneous bids. An independent private-values bidding model is employed to endogenously determine an optimal cost allocation; we term such a cost allocation “implicit.” The optimal implicit fixed cost allocation is shown to fully allocate fixed costs ex ante, although the fixed costs may be under, over, or exactly allocated ex post.